HEB is required for the specification of fetal IL-17-producing γδ T cells - Tracy S. H. In (Nature Portfolio, 2017)
The γδ T cell pool includes abundant IL-17-producing cells that protect mucosal surfaces, but the signals that control γδ T cell specification are unclear. Here the authors identify a role for the transcription factor HEB, and antagonistic activity of Id3, in the development of these cells.